The Use of Soxhlet Techniques in the Essential Oil Extraction from Anise Seeds (Pimpinella anisum) - Arifah Sukasri; Wahyu Budi Utomo; Rahmiah Sjafruddin; Muhammad Nursam (Program studi Teknik Kimia UNS, 2023)
Abstract. Anise seeds can be processed into essential oils by steam distillation and solvent extraction. This research aims to produce a high oil yield by determining the optimum conditions of extraction, extracting anise seeds according to optimum conditions, producing anise oil with good quality based on 90% alcohol solubility analysis, analyzing the acid number, and conducting GC-MS analysis. The Activity Method was carried out by determining the optimum conditions of extraction on the effect of the variation in the ratio between anise seed powder and petroleum ether. Furthermore, based on optimal conditions, extraction was carried out at a temperature of 60°C, 5 hours with 5 repetitions. The results of essential oils were analyzed including solubility analysis, oil acid number, and GC-MS. The optimal extraction conditions were obtained at the ratio of anise seeds and petroleum ether 1:12.5 with an average oil yield of 4.72%. The results of the analysis showed that anise oil had good quality based on the oil solubility in 90% alcohol with a 1:7 ratio. The acid number of anise seed oil was obtained at 1.14444. GC-MS analysis showed that anise seed oil contained estragol, anethole, limonene, fenchone, and anis ketone.Keywords:Anise seeds, essential oil, soxhlet, GC-MS